2020
DOI: 10.1515/ijamh-2019-0088
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with smoking among Tunisian secondary school-adolescents

Abstract: AbstractObjectivesThis study aimed to estimate the extent of smoking experience among high and middle school adolescents in Southern Tunisia and to delineate its potential associated factors.MethodsWe conducted a cross-sectional study among middle and high school-ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Sex differences, along with the time of onset, may be related to the earlier age of puberty onset and growth spurt, and to the different distribution of adipose tissue and body composition. 17 Females are more likely to be overweight during adolescence, with a peripheral adipose tissue distribution, while abdominal visceral fat accumulation is more common among males. 18 According to a previous population-based prospective cohort study, overweight was associated with incident LBP rather than with persistent LBP in both sexes.…”
Section: Epidemiology Of Lbp In Children and Adolescentsmentioning
confidence: 99%
“…Sex differences, along with the time of onset, may be related to the earlier age of puberty onset and growth spurt, and to the different distribution of adipose tissue and body composition. 17 Females are more likely to be overweight during adolescence, with a peripheral adipose tissue distribution, while abdominal visceral fat accumulation is more common among males. 18 According to a previous population-based prospective cohort study, overweight was associated with incident LBP rather than with persistent LBP in both sexes.…”
Section: Epidemiology Of Lbp In Children and Adolescentsmentioning
confidence: 99%
“…Following this, the neck exhibits a prevalence of 18%, while both the knees and shoulders demonstrate a comparable incidence of 17%. According to the World Health Organization (WHO) Global Burden of Disease research, neck discomfort and other musculoskeletal illnesses were ranked 4th and 10th, respectively [8,9]. The prevalence of pain in the neck, lower back, shoulder, elbow, and wrist is higher among individuals aged 45-64, but pain in the hip, knee, ankle, and foot is more prevalent in older age cohorts [8].…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization (WHO) Global Burden of Disease research, neck discomfort and other musculoskeletal illnesses were ranked 4th and 10th, respectively [8,9]. The prevalence of pain in the neck, lower back, shoulder, elbow, and wrist is higher among individuals aged 45-64, but pain in the hip, knee, ankle, and foot is more prevalent in older age cohorts [8]. Conversely, it has been found that osteoarthritis of the hip, osteoporosis, rheumatoid arthritis, and fibromyalgia exhibit the lowest levels of health-related quality of life (QoL).…”
Section: Introductionmentioning
confidence: 99%
“…And is closely related to poor mental state, vulnerable to psychological factors, living habits and other factors, may also be an important factor leading to adult cervical and lumbar diseases, continue to the work stage, so it is urgent to understand its potential risk factors and implement effective prevention and intervention measures. This study explored the influence and intervention strategies of adolescent patients with neck, shoulder and back pain [1].…”
Section: Introductionmentioning
confidence: 99%